Wiener Index of Intuitionistic Fuzzy Graphs with an Application to Transport Network Flow. (14th May 2022) - Naeem, Tulat; Jamil, Muhammad Kamran; Fahd, Khawaja Muhammad; alAmeri, Abdu
Abstract : The Wiener index WI is one of the connectivity parameters used to know the biochemical and physicochemical properties of compounds depending upon their molecular structures. Intuitionistic fuzzy graphs IFG s are a convenient tool to represent the objects and relations between them with two types of information using truth membership degree and falsity membership degree. This research work presents the concept of WI under the structure IFG s, I F trees, and I F cycles. Some bounds on WI are investigated. The relationship between WI and connectivity index CI is also studied. In the end of this study, an application of the WI in transport network flow is proposed.